VWF excess and ADAMTS13 deficiency: a unifying pathomechanism linking inflammation to thrombosis in DIC, malaria, and TTP - Schwameis, Michael; Schörgenhofer, Christian; Assinger, Alice; Steiner, Margarete M.; Jilma, Bernd (Thrombosis and Haemostasis, 2015)
Absent or severely diminished activity of ADAMTS13 (A Disintegrin And Metalloprotease with a ThromboSpondin type 1 motif, member 13) resulting in the intravascular persistence and accumulation of highly thrombogenic ultra large von Willebrand factor (UL-VWF) multimers is the pathophysiological mechanism underlying thrombotic thrombocytopenic purpura. Reduced VWF-cleaving protease levels, however, are not uniquely restricted to primary thrombotic microangiopathy (TMA), e. g. thrombotic thrombocytopenic purpura, but also occur in other life-threatening thrombocytopenic conditions: severely decreased ADAMTS13 activity is seen in severe sepsis, disseminated intravascular coagulation (DIC) and complicated malarial infection. The clinical relevance of these secondary thrombotic microangiopathies is increasingly recognised, but its therapeutic implications have not yet been determined. The presence of a secondary TMA in certain diseases may define patient groups which possibly could benefit from ADAMTS13 replacement or a VWF-targeting therapy. This short-review focuses on the role of UL-VWF multimers in secondary TMA and discusses the potential of investigational therapies as candidates for the treatment of TTP. In conclusion, prospective clinical trials on the effectiveness of protease replacement in vivo seem reasonable. Carefully selected patients with secondary TMA may benefit from therapies primarily intended for the use in patients with TTP.
Keywords: ADAMTS13; VWF; TTP; DIC; sepsis; malaria